Indicators chest rheography at swimmers at rest and after exercise in different body positions - Синюгіна Марія Борисівна (Mariya Sinyugina); Дьомiн Сергiй Сергiйович (Sergii Dyomin) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: Study of chest rheography for skilled swimmers when the dosage of physical activity in different body positions. Materials and Methods: the study involved 20 qualified swimmers for middle and long distance. Results: studies changes rheographic indicators from qualified swimmers in response to exercise in different positions of the body showed a clear dependence of the structure and functional hemodynamic changes the position of the body in which the exercise is carried out. Conclusions: found that when evaluating the success of readiness of swimmers and planning training loads must be based on indicators of physical performance obtained during exercise in a horizontal position of the body.